DEVELOPMENT OF NEURITE OUTGROWTH FOLLOWING DIFFERENTIATION OF MOTOR NEURON-LIKE CELL LINE, NSC-34 BY DIFFERENT CONCENTRATIONS OF RETINOIC ACID - Nor Alia AA; Muhammad Fauzi D; Yogeswaran L; Muhammad Da'in Y; Jalilah I (Asian Journal of Medicine & Health Sciences, 2021)
Background: Glutamate excitotoxicity is one of the critical causes of motor neuron degeneration, a common hallmark in movement-related disorders. For the past decades, experimental model systems have been focusing on using animal models to elucidate the pathophysiology of neurodegeneration. However, the usage of animals is costly, time-consuming, and has ethical implications. Cell culture models such as the NSC-34 cell line, a mouse motor neuron-like hybrid cell, can serve as an alternative study system to overcome these limitations. NSC-34 cell line can be differentiated to express motor neuron properties using simple chemical treatments. The study reports on optimizing the differentiation protocol for NSC-34 cells using retinoic acid treatment. Methods: NSC-34 cells were seeded onto a 12-well plate and grown in retinoic acid-containing media (1µM or 10µM). Cells were incubated for seven days in a humidified atmosphere with 5% CO2 at 37°C. Cells were analyzed using an immunocytochemical technique for Beta-III tubulin (neuronal biomarker) and DAPI (nuclei marker). Cells were imaged were using phase-contrast microscopy and fluorescence microscopy. Results: Neurite outgrowth was evident in both retinoic acid concentration groups. However, after seven days in culture, the projection of neurites in the 10µM retinoic acid group was more extensive than the 1µM group. Conclusion: The present study supports the use of retinoic acid treatment at 10µM concentration as an efficient differentiation of NSC-34 cells into motor neurons. This method sees its application in experimentation for studying axonal transport and electrical impulse conductivity.